The analysis of students' critical problem solving on circle-related questions using pesantren-based scientific approach. (February 2020) - Kriswanto, A; Susanto; Irvan, M
Abstract: The objective of this study was to analyze students' critical thinking skills in solving problems concerning circle material using pesantren-based scientific approach. This research employed qualitative descriptive approach, which involved students at class VIII of Plus Junior High School of Darussalam Blokagung Banyuwangi. The instruments used in this study included lesson plan, worksheet, achievement test, critical thinking ability assessment sheets, and questionnaires. From the instrument validation, the average score of each instrument was 3.87; 3.69; and 3.83 for lesson plan, worksheet, and achievement test. The data on students' learning activities demonstrated the increase in their critical thinking skills. In the first meeting, 77.27% of the students achieved "Good" category. In the second meeting, 89.77% of them gained "Very Good" category, and in the third meeting 92.04% of the students were at "Very Good" category. With respect to the students' learning outcome, which was set at 75 points, most of them were successful in achieving the minimum passing criteria in that 28 students (87.5%) satisfied the criteria, while 4 students (12.5%) failed. In addition, the analysis on observation data germane to students' critical thinking skills also demonstrated an increase. In the first meeting, 65% of the students were at "Good" category. 72.5% of the students achieved "Good" category in the second meeting, and in the third meeting 85% of the students were at "Very Good" category. The results of the data analysis showed that students' critical thinking skills in the solving circle-related questions using pesantren-based scientific approach indicated the achievement at "Very Good" criteria.